2019
DOI: 10.1088/1361-6560/aaf9c9
|View full text |Cite
|
Sign up to set email alerts
|

Can CT imaging improve targeting accuracy in clip-based proton therapy of ocular melanoma?

Abstract: To evaluate the benefit of adding CT imaging to the simulation process of clip-based proton therapy of ocular melanomas. For thirty ocular melanoma cases, the clip position in the eye model was determined based on orthogonal radiographs as well as on a CT image set. The geometrical shift of the clips between the standard simulation process and standard simulation process with addition of CT imaging (CT-guided) was determined. The dosimetric impact was evaluated by developing treatment plans based on both the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…At the Helmholtz-Zentrum Berlin für Materialien und Energie (HZB) in Berlin, for example, volumetric eye imaging has been integrated in their in-house treatment planning system (TPS; OCTOPUS) [7][8][9][10]. Slopsema et al also argue for using CT imaging to improve the geometrical eye model and Marnitz et al [11] report reductions of target volumes by close to two when comparing fiducial based definition to delineation in MRI scans [3]. In contrast, Daftari et al [9] found more similar volume ratios of between 0.993 and 1.02 for delineations using EyePlan or T2weighted MRI imaging [12].…”
mentioning
confidence: 99%
“…At the Helmholtz-Zentrum Berlin für Materialien und Energie (HZB) in Berlin, for example, volumetric eye imaging has been integrated in their in-house treatment planning system (TPS; OCTOPUS) [7][8][9][10]. Slopsema et al also argue for using CT imaging to improve the geometrical eye model and Marnitz et al [11] report reductions of target volumes by close to two when comparing fiducial based definition to delineation in MRI scans [3]. In contrast, Daftari et al [9] found more similar volume ratios of between 0.993 and 1.02 for delineations using EyePlan or T2weighted MRI imaging [12].…”
mentioning
confidence: 99%
“…Nevertheless, those geometrical models may in some cases significantly differ from the real patient anatomy. Slopsema et al 18 recently evaluated the differences in clip position between an eye definition based on geometrical modeling as provided by the EYEPLAN TPS and a modified eye model based on CT‐guided simulation. They demonstrated that the position of the clips is more accurately modeled for specific cases in the latter when 3D CT information was incorporated.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical workflow, including surgery for clips placement, in‐room simulations and positioning, planning and treatment completions, has been described in detail by a wide spectrum of publications over the last four decades 8,14–18 . In short, patients undergo surgery prior to proton therapy, with clips stitched onto the sclera to outline the tumor boundary.…”
Section: Introductionmentioning
confidence: 99%
“…Slopsema et al [20] showed that the shape change of the eye due to gravity is less than 0.6 ± 0.3 mm, by comparing the tantalum clip positions on supinely acquired CT images, with clip positions obtained from a geometrical eye-model based on orthogonal X-rays acquired in sitting position. As this observed difference is probably largely the result of uncertainties in the geometrical eye-model used for PBT planning, such as the rotational center of the eye, the actual change in eye shape is expected to be less than the observed differences between the CT-based and X-ray based eye-model.…”
Section: Discussionmentioning
confidence: 99%